1997
DOI: 10.1055/s-2007-972663
|View full text |Cite
|
Sign up to set email alerts
|

The Validity of the Telemetric System CORTEX X1 in the Ventilatory and Gas Exchange Measurement during Exercise

Abstract: With the portable spirograph CORTEX X1 both the oxygen consumption and the carbon dioxide output can be determined. Therefore, the aim of the present study was to determine the accuracy of the CORTEX X1 in measuring F(E)O2, F(E)CO2 and V(E) when attached to a motor-driven mechanical syringe and to validate the CORTEX X1 against a standardized breath-by-breath system during a graded bicycle ergometry. Fifteen subjects (8 male, 7 female; 26.7+/-3.3 years) performed two graded exercise tests on a bicycle ergomete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 0 publications
3
22
0
Order By: Relevance
“…We used a lightweight, validated (25), portable telemetric system to collect metabolic data on a breath-by-breath (BXB) basis during all tests (V MAX ST, Sensormedics Corp.). This system utilizes a turbine digital volume transducer, an electrochemical O 2 -analyzer and an infrared CO 2 -analyzer.…”
Section: Ee Using Standard Exhaled Breath Metabolic System (Ee-bxb)mentioning
confidence: 99%
“…We used a lightweight, validated (25), portable telemetric system to collect metabolic data on a breath-by-breath (BXB) basis during all tests (V MAX ST, Sensormedics Corp.). This system utilizes a turbine digital volume transducer, an electrochemical O 2 -analyzer and an infrared CO 2 -analyzer.…”
Section: Ee Using Standard Exhaled Breath Metabolic System (Ee-bxb)mentioning
confidence: 99%
“…The validity of this system has been determined previously against a common breath-bybreath system (OXICONgamma, Mijnhardt, Bunnik, The Netherlands) during graded cycle ergometry (Schulz et al 1997). The weight of the mobile device, including mask and backpack, was 4.5 kg.…”
Section: Measurements and Analysesmentioning
confidence: 99%
“…Thus, a systematic error cannot be completely excluded by the validation of Schulz et al (1997). The validity of _ V O 2ten becomes quite dependent upon a correct alignment of the gas concentration measurements with thē ow measurements under intermittent exercise conditions (Lamarra and Whipp 1995).…”
Section: Measurements and Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, others have suggested that the ideal experimental design when validating metabolic measurement systems would have simultaneous breath-by-breath data collection [11]. The CPX/D has been successfully used as a reference system during rest and varying intensities of exercise elsewhere [7,9,22,23]. …”
Section: Validity Of the Standard System For Comparisonmentioning
confidence: 99%